Numerical study of heat and mass transfer enhancement in Prandtl fluid MHD flow using Cattaneo-Christov heat flux theory. (May 2022) - Salmi, Abdelatif; Madkhali, Hadi Ali; Ali, Basit; Nawaz, M.; Alharbi, Sayer Obaid; Alqahtani, A.S.
Abstract: Heat and mass transfer have numerous industrial applications. The classical heat and mass transfer laws (Fourier and Fick laws) do not predict thermal and solute relaxation time phenomena. However, in this article, generalized modeling related to simultaneous heat and mass transfer in non-Newtonian fluid in the presence of chemical reaction and heat generation is presented and models are numerically solved by the finite element method (FEM). Hybrid nanoparticles A g and F e 3 O 4 are considered and novel correlations are inserted during numerical simulations. The present results have a good agreement with already published benchmark. Thermal relaxation time is the characteristics of the fluid due to which it avoids or tries to avoid the thermal changes. The fluid with thermal relaxation characteristic tries to restore the thermal equilibrium and hence the temperature of the fluid is decreased. The solute relation is incorporated in the concentration equation from generalized Fick's law and solute relaxation time has shown a decreasing tendency in the concentration field. The solute boundary layer region can be controlled via an increase in the solute relaxation parameter. Ohmic dissipation in hybrid nanofluid A g − F e 3 O 4 − Prandtl fluid) is stronger than that in mono nanofluid ( A g − Prandtl fluid). Hybrid nanofluid ( A g − F e 3 O 4 − Prandtl fluid) produces more heat due to Joule heating than that produced by mono nanofluid ( A g − Prandtl fluid).